Allergic rhinitis – a review of current diagnostic and therapeutic methods - Kwiliński, Kacper; Kucharska, Maja; Szyszka, Monika; Wawrzyńska, Barbara; Przybysz, Paulina; Paruch, Agata; Wadowska, Magdalena (Quality in Sport, 2024)
Allergic rhinitis (AR) is a common disease characterized by inflammation of the nasal mucosa caused by exposure to allergens such as pollen, house dust mites, animal dander, and molds. Symptoms include sneezing, nasal itching, watery discharge, and nasal congestion, often associated with conjunctivitis. AR can significantly reduce patients’ quality of life, affecting their ability to perform daily activities and causing sleep disturbances and fatigue. Diagnosis of AR is based on a past medical history, assessment of clinical symptoms, and allergy tests, such as skin tests, and measure of specific class E (IgE) immunoglobulins in blood serum level. Treatment includes allergen avoidance, pharmacotherapy, and allergen immunotherapy. Antihistamines, intranasal glucocorticosteroids, cromones, and anti-leukotriene drugs are the basis of pharmacotherapy, helping to control symptoms and improve a patient’s quality of life. Allergen immunotherapy, both subcutaneous and sublingual, is effective in modifying the course of the disease and reducing hypersensitivity to allergens. New therapeutic and diagnostic approaches, such as biomarkers and biologics, are under investigation and may offer more personalized and effective AR treatment in the future. A holistic approach to AR, including patient education and lifestyle modification, is crucial for long-term therapeutic success. The article aims to review current diagnostic and therapeutic methods used in AR.